THE WINNING STRATEGY OF THE PROSPEROUS JUSTICE PARTY (PKS) IN EAST LAMPUNG REGENCY IN THE 2029 ELECTION THROUGH THE IMPLEMENTATION OF THE DATA-DRIVEN CAMPAIGN APPROACH - Yusnadi; Riswan (International Journal of Multidisciplinary Reseach, 2026)
Political campaigning is undergoing a major transformation through data-driven strategies that predict voter behavior, segment target audiences, and optimize political communication. In Indonesia, data-driven campaign (DDC) methods are increasingly used by political parties seeking competitive advantages in regional elections. This study analyzes the winning strategy of the Prosperous Justice Party (PKS) in East Lampung Regency for the 2029 Election by examining the design and implementation of DDC principles to improve voter outreach and electoral performance. Using a qualitative descriptive method, the study draws on document analysis, interview data, and secondary sources to identify stages of strategic planning, voter profiling, digital mobilization, and field operations. The findings indicate that PKS leveraged voter databases, demographic clustering, behavioral analytics, digital engagement metrics, grassroots reports, and targeted messaging to influence voter preferences more effectively. The study concludes that DDC strengthened PKS’s organizational preparedness, message precision, campaign efficiency, and capacity to build competitive electoral strategies while navigating ethical and regulatory challenges.